Biocontrol of Two Escherichia coli O157:H7 Strains and a Nonpathogenic Surrogate E. coli in Wheat Grains and Wheat Milling Operations Using a Lytic Bacteriophage Cocktail - Amit Vikram; Kristen McCarty; Mary T. Callahan; Joanne Sullivan; Alexander Sulakvelidze (Journal of Food Protection)
Shiga toxin-producing Escherichia coli (STEC) contamination of wheat and flour has emerged as a significant public health risk and a major challenge for the milling industry. Several interventions such as chlorine, chlorine dioxide, ozone, lactic acid, etc. have been evaluated and are used with variable success. Phage biocontrol has emerged as an effective strategy for controlling foodborne pathogens in various foods. This study examined the efficacy of phage biocontrol in mitigating Escherichia coli O157:H7 contamination in soft wheat milling operations. The findings demonstrated the efficacy of phage applications in reducing E. coli O157:H7 on wheat while maintaining flour quality and sensory attributes. Laboratory tests showed that the phage cocktail reduced E. coli O157:H7 populations by up to 1.3 log CFU/g within 4 h on wheat grains, with reductions correlated to phage concentrations. In mill trials, tempering soft wheat with phage cocktail at three concentrations i.e. 1 × 106 PFU/g, 2.5 × 106 PFU/g, and 1 × 107 PFU/g resulted in significant reductions in populations of a nonpathogenic E. coli O88 strain, ranging from 1.4 to 3.1 log CFU/g, in a dose-dependent manner. Tempering with phage reduced the E. coli populations throughout the milling operation. Two different tempering systems, the DAMPE system and the Bühler Turbolizer, were evaluated. Both systems achieved similar overall reductions, although the DAMPE system showed slightly higher efficacy than the Bühler Turbolizer after 6 h of tempering. Additionally, phage treatments reduced positive samples in straight-grade and patent flours by 15–29%. Importantly, solvent retention capacity and hydration performance of phage-treated flour were unaffected, and sensory tests indicated no changes in flavor, texture, or appearance of baked products, including cookies and pancakes. These findings confirm that phage applications effectively reduce foodborne pathogens on wheat without compromising product quality.